Chess square table from machining wood waste / Nur Hannani Abdul Latif ...[et al.] - Abdul Latif, Nur Hannani; Kamarudin, Norashikin; Ahmad Zaki, Junaiza; Zakaria, Shaikh Abdul Karim Yamani; Othman, Ahmad Fauzi; Shafie, Amran; Affendy, Amy Saiful (2016)
Machining wood waste may be occured due to several numbers of factors such as split end, left over, rejects from cut up and drying defects on timber. So, it is important to explore the best solution in managing machining wood waste, as now it becoming increased and may affect others. Hence, wasting is also prohibited in Islam, as it means that a thing was not fully utilized. Improper machining wood waste management can cause pollution to the environment and may affect others comfortability and health. In this study, machining wood waste (long-off cut and short-off cut) from different wood species was used as a raw material. The objectives of this study was to design and produce a Chess Square Table at lower production cost by using machining wood waste. A survey (set of questionnaires was undertaken to evaluate the properties of the product after completely designed and manufactured. It was distributed to 85 correspondents (in UiTM) based on gender and range of age. The properties that been evaluated were suitability of material, design, aesthetic values, ergonomics and anthropometrics, commercialization and price. Result shows that there is no significant different on the evaluation based on gender and range of age. It is proven that machining wood waste can be value added by turned them out into furniture, thus producing new product at lower production cost and reducing their amount. Overall, Chess Square Table has great potential to be commercialized in the furniture industry in Malaysia.